Renewal from Different Directions: The Case of UNITE-HERE Local 75 - Tufts, Steven (Paths to Union Renewal: Canadian Experiences, 2006)
[This] study is important for many reasons. it relates to a large local of workers in major hotels in Toronto, owned by multinational firms. The workforce consists largely of immigrant and visible minority women with poor wages and working conditions. As Tufts points out, the gender, ethnic and income segmentation of the hotel labour market creates difficult challenges for building union solidarity and for new organizing and effective bargaining. In this context, Local 75's experience with organizing and pattern bargaining is instructive. --Editors' introduction
Keywords: Hotel and hospitality workers; Labor Unions; Labor movement; Organizational change; Toronto; Unite-HERE. Local 75